Home health care routing and scheduling: A review. (January 2017) - Fikar, Christian; Hirsch, Patrick
Abstract: In home health care (HHC) operations, nurses are scheduled and routed to perform various services at clients' homes. As this often requires a combination of vehicle routing and scheduling approaches, resulting optimization problems are complex and, hence, of high interest to stakeholders such as researchers, practitioners and policy-makers. With demand for HHC expected to increase substantially, future work is essential to decrease costs and to guarantee service quality. In this review, we provide a comprehensive overview of current work in the field of HHC routing and scheduling with a focus on considered problem settings. Recent advances in HHC optimization are highlighted and future research directions discussed. Abstract : Graphical abstract: Abstract : Highlights: This review investigates recent work on home health care routing and scheduling. A comprehensive overview with a focus on considered problem settings is given. Single-period and multi-period problems are differentiated. Results highlight a heterogeneous research field of public interest. Recent advances and future research directions are discussed.